2022
DOI: 10.47836/pjssh.30.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Portrayals of Child Sexual Abuse of Urdu Newspapers in Developing Countries

Abstract: Child sexual abuse is serious in any developing country confronting children’s sexual exploitation. Certain factors are liable for fostering child sexual abuse, and the media can play a significant role in eradicating this issue. This research scrutinized the portrayals of child sexual abuse in three Urdu-Pakistani newspapers by analyzing the role of the newspapers concerning the burgeoning prevalence of child sexual abuse based on seven categories proposed by UNICEF. The data were generated in 2019 using a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The study problem and objectives were kept under consideration while analyzing the data. Data analytical techniques are applied through the development of a content coding sheet (Habes et al, 2022). The foundation for framing theory in table 4.1 is used to build the coding sheet.…”
Section: Discussionmentioning
confidence: 99%
“…The study problem and objectives were kept under consideration while analyzing the data. Data analytical techniques are applied through the development of a content coding sheet (Habes et al, 2022). The foundation for framing theory in table 4.1 is used to build the coding sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to the questionnaires were collected using a 7-point Likert scale. (Al Olaimat et al, 2022;Habes et al, 2021;Habes, Elareshi, et al, 2022) The questionnaire has been adapted from previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, the instrument was checked for normality, then the external model was tested, and once it was confirmed that the external model was suitable, Smart PLS3 was used to analyze the internal model after it had been confirmed that the external model was suitable. (Habes, Al-Adwan, et al, 2022;Habes, Ali, et al, 2022;Wang et al, 2022).The procedures that have been followed for analyzing the collected data are mentioned in the analysis portion.…”
Section: Methodsmentioning
confidence: 99%